The effect of pentoxifylline on cerebral vasospasm following experimental subarachnoid hemorrhage. (2nd September 2021) - Bahadir, Sinan; Narin, Firat; Başar, Ibrahim; Hanalioğlu, Şahin; Bilginer, Burçak; Akalan, Nejat
Abstract: Objects: Cerebral vasospasm is an important event that occurs following subarachnoid hemorage which has significant mortality and morbidity. The goal in this study was to investigate the effect of pentoxifylline on vasospasm in an experimental subarachnoid hemorrhage model. Methods: In this study, 20 male New Zeland White rabbits weighing 3000–3500 g were assigned randomly to four groups. Animals in group 1 served as controls. Animals in group two received only intravenous pentoxifylline injection 3 times in 12 h intervals. In group 3, SAH was induced and no injection was given. Animals in group 4 received intravenous pentoxifylline (6 mg/kg) injections 3 times at 12 th, 24 th and 36 th hours after subarachnoid hemorrhage induction. All animals were sacrificed and basilar arteries were removed at 48th hour. Basilar artery vessel diameters, wall thicknesses and luminal section areas were measured with Spot for Windows version 4.1. Statistical analysis was performed using ANOVA and Kruskall–Wallis tests. Results: Mean basilar artery luminal section areas and luminal diameters in group 4 were significantly higher compared to group 3 ( p  < 0.05). Basilar artery wall thicknesses and were found to be higher in group 3 than in other groups and this was also statistically significant ( p  < 0.05). Conclusion: Our study demonstrated that intravenous administration of pentoxifylline significantly decreases vasospasm after subarachnoid hemorrhage.